Best practices in the agrochemical industry - Cheremisinoff, Nicholas P. (Handbook of pollution prevention and cleaner production, 2010)
"Best practices in the agrochemical industry covers the impact of agrochemicals in food and water supplies, and provides an overview of agrochemical residues and their health impacts as well as mitigation strategies. It includes extensive data tables covering USA and international regulatory frameworks for exposure to pesticides, including EPA, NIOSH, OSHA, WHO and ACGIH. Health impacts are explored, such as the pollution of drinking water with atrazine, trichloropropane and DBCP and the risks associated with these substances, including miscarriages and infertility. The authors also explore the effect of pesticide residues in food, including contaminants in organic food, and they present a case study concerning worker pesticide exposure. This book is a guide and professional reference for those involved in the agrochemical industry and it details safer manufacturing processes and procedures to limit pollution"--Page 4 of cover